CHRNA5/CHRNA3 gene cluster is a risk factor for lumbar disc herniation: a case-control study - Xuejun Yang; Xiaodong Guo; Zhi Huang; Yifeng Da; Wenhua Xing; Feng Li; Manglai Li; Ke Sun; Haiyu Jia; Yong Zhu (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Lumbar disc herniation, a type of chronic low back pain syndrome, is caused by the lumbar intervertebral disk degeneration. Genetic variation in the CHRNA5/CHRNA3 has shown strong associations with smoking-related diseases. This study’s aim is to test whether single-nucleotide polymorphisms in the CHRNA5/CHRNA3 gene are associated with lumbar disc herniation risk. Methods The genotype frequency distributions of the polymorphisms were detected by polymerase chain reaction-restriction fragment length polymorphism in 380 lumbar disc herniation patients (case group) and 400 healthy individuals (control group). Allelic, genotypic, and haplotype analyses were performed. Results We found that the individuals with rs8040868 CT genotype had a 0.46-fold higher risk of lumbar disc herniation than those with rs8040868 TT genotype, in men group (OR = 0.46, 95% CI 0.25–0.84, p = 0.012). Also among women, rs8040868 CT + CC genotype still reduced the risk of lumbar disc herniation under the dominant model (OR = 0.50, 95% CI 0.28–0.89, p = 0.019). Haplotype analysis showed that compared with the CHRNA5 “TACAACCG” wild-type, the “TACACCCG” haplotype was found to be associated with a decreased risk of lumbar disc herniation (LDH) (OR = 0.79, 95% CI 0.63–1.00, p = 0.047), while, in the less than 50-year-old group, CHRNA5 “TACACCCG” increased the risk of LDH (OR = 1.46, 95% CI 1.01–2.13, p = 0.047). Conclusions Our data suggest that gene variance in the CHRNA5/CHRNA3 is associated with risk of lumbar disc herniation in the case-control study.